Lower bile duct metastasis from rectal cancer after surgery for liver metastasis and intrahepatic bile duct metastasis: a case report - Nakagawa, Yoichi (BMC Surg, 2020)
BACKGROUND: Biliary metastasis of colorectal cancer is a manifestation of metastatic liver carcinoma, and is often difficult to differentiate from cholangiocarcinoma. Further, lower bile duct metastasis of colorectal cancer is rare. We report the case of a 74-year-old woman who underwent pylorus-preserving pancreatoduodenectomy for lower bile duct metastasis of rectal cancer. CASE PRESENTATION: The patient had undergone laparoscopic low anterior resection for rectal cancer (pT3N0M0 stage IIA) 6 years ago, laparoscopic anterior liver resection for liver metastasis (Couinaud segment V) 3 years ago, and left and caudal lobectomy with extrahepatic bile duct resection for left intrahepatic bile duct metastasis 6 months ago. A follow-up examination showed a 15 mm mass in the common bile duct, for which she underwent pylorus-preserving pancreatoduodenectomy. Histological and immunohistological examination of the specimens revealed similar cytokeratin (CK) expression patterns, which were negative for CK7 and positive for CK20. Therefore, the definitive diagnosis was metastasis from rectal cancer. CONCLUSIONS: In summary, we encountered a case of lower bile duct metastasis from rectal cancer, which is often difficult to differentiate from cholangiocarcinoma. In such patients, CK7 and CK20 expression patterns are important in differentiating the two. The mechanism of metastasis in this case was considered to be through cancer cell implantation from lymphatic spread, or through distant metastasis of the primary cancer.